Isolation of Flavonoid Compound and Antioxidant Activity of Salix tetrasperma Roxb. Leaves - Ria Januarti; Adlis Santoni; Mai Efdi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Salix Tetrasperma Roxb. is a plant that found in Indonesia were used as traditional medicine such as diabetes and wound healing. In this study, a flavonoid compound of the ethyl acetate extract of Salix tetrasperma Roxb. leaves was isolated by chromatography technique and the antioxidant activity was determined by DPPH assay. The isolation led to obtain 5,7-dihydroxy-3'-methoxyflavone based on NMR spectra. The ethyl acetate extract exhibited the highest antioxidant activity with the IC50 is 65.89 µg/mL. This study shows that the Salix tetrasperma Roxb. has good potential as source of antioxidant agent.